Vida e Obra do Professor Afonso Guimarães - Fernando Paulo Gomes e Silva (2021)
José Afonso Dias Guimarães was born in Porto at the beginning of the XX century and was a Portuguese researcher and notable figure of the Porto Medical Faculty. He worked at the Lisbon Physiology Institute, the Institut Solvay de Physiologie, in Brussels, and the National Institute for Medical Research, in London, with researchers such as Abel Salazar, Marck Athias, Jean Demoor and Henry Dale. He developed works in the field of sexual glands internal secretions, salivary secretion, blood pressure and neurotransmission mediators. Afonso Guimarães was a full Professor of Physiology, Director of the Service of Physiology of the Porto Medical Faculty and is accepted as the founder of the Physiology Laboratory of the Medical Faculty of Porto. He also practiced medicine, was Clinical Director of Chaves Thermal Spa and Director of the Physiopathology Service of Saint John's Hospital, in Porto, duties that he performed with characteristic dedication and competence. He was an eloquent communicator, cultured, bibliophile, and Art collector. Afonso Guimarães promoted research as a duty of the university professor and encouraged others to do research. He will always be remembered as a person of many qualities, an inspiring example, and a defender of Science and those that study it.